Resources for an early, creative and inclusive music education (Tabanque. Revista Pedagógica, 2018)
Some resources are presented in this article that encourage early musical education, creativity, inclusive, to reach everyone significantly
Keywords: Creative Methods; Pedagogie musicale d'éveil; music therapy; music technology; inclusive music education